Ethics Is Not Rocket Science: How to Have Ethical Discussions in Your Science Class - Kelly C. Smith (American Society for Microbiology, 2014)
The Rutland Institute for Ethics at Clemson University seeks to encourage discussion on campus, in businesses, and in the community about how ethical decision-making can be the basis of both personal and professional success. In the last 15 years, our fellows have, among other things, served as Co-PI’s on a wide range of grants, produced Responsible Conduct of Research training for science and engineering graduate students and faculty, managed the ethics curriculum at a medical school, and produced video lectures on ethical thinking for undergraduate Biology majors. The crown jewel of our efforts to-date is our Ethics Across the Curriculum program, affectionately known as “ethics boot camp.” Each year, we bring faculty from all corners of the disciplinary spectrum together to show them how to have rich ethical discussions in their own classes with the students from their majors. The program has been extremely successful and over the past 15 years has touched the lives of hundreds of faculty and thousands of students. The purpose of this paper is to provide a very abbreviated version of the Rutland Ethics Across the Curriculum material to a wider audience of science educators. It is our hope that this will motivate more faculty to introduce ethics into their classes as well as provide them the basic tools they will need to make this experience fruitful for all concerned.